Criminal Liability for Fossil Sellers and Buyers as Protected Cultural Heritage Under the Law: A Case Study in Bojonegoro - Ayu Wulandari; Andrianto Prabowo; Dodik Wahyono (Jurnal Hukum In Concreto, 2026)
The preservation of fossils as part of cultural heritage in Indonesia continues to face various challenges, particularly those related to the low level of public legal awareness and the suboptimal implementation of law enforcement. Fossils that possess significant historical and scientific value are frequently transferred without complying with the applicable statutory provisions, thereby posing a risk to the preservation of national cultural heritage. This study aims to analyze the criminal liability of both sellers and buyers of fossils classified as protected cultural heritage, as well as to examine the enforcement of criminal law against such practices in Bojonegoro Regency. The research applies theories of criminal liability and cultural heritage protection, supported by a review of statutory regulations and scholarly legal opinions. This study employs a normative-empirical legal research method using statutory, conceptual, and empirical approaches. Data were collected through literature review and interviews. The findings indicate that both sellers and buyers of fossils may be held criminally liable under Law Number 11 of 2010 concerning Cultural Heritage; however, its implementation has not been carried out optimally. The study concludes that strengthening law enforcement and increasing public legal awareness are necessary to ensure the protection of fossils as part of cultural heritage.